Innkeeper at the Roach Motel - Salo, Dorothea (My University, 2007)
Library-run institutional repositories face a crossroads: adapt or die. The "build it and they will come" proposition has been decisively proven wrong. Citation advantages and preservation have not attracted faculty participants, though current-generation software and services offer faculty little else. Academic librarianship has not supported repositories or their managers. Most libraries consistently under-resource and understaff repositories, further worsening the participation gap. Software and services have been wildly out of touch with faculty needs and the realities of repository management. These problems are not insoluble, especially in light of Harvard University arts and science faculty's recent permissions mandate, but they demand serious reconsideration of repository missions, goals, and means if we are to be ready for Harvard imitators, and especially to be ready should those imitators not surface.
Keywords: institutional repositories; open access